SUDDEN SENSORINEURAL HEARING LOSS AND COVID-19 - Awang Hamat, Ain Saffiya; Hasram, Izzatul Umairah Muhammad; Alwi, Husna Sofia; Izanee, Husna Wahdina; Razali, Najwa Mohd; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Allam, Amirah Hannan Alaa Eldin; Md Tajudin, Huriyyah Hamiemah; Jaffer, Usman (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Sudden sensorineural hearing loss (SSNHL) is an auditory condition that happens rapidly and may result in a permanent hearing impairment. Increasing evidence suggests a potential link between SSNHL and viral infections, including COVID-19. This review examines the association between sudden sensorineural hearing loss and COVID-19 by synthesizing past literatures to identify pathophysiological mechanisms, clinical outcomes and management implications. While some studies supported the association between COVID-19 and SSNHL, others report conflicting findings, highlighting the need for further investigation. Hence, understanding this link is pertinent for improving diagnostic and treatment strategies for SSNHL, with broader implications for the post COVID-19 era.